Pendampingan UMKM Pengelolaan Keripik Pisang di Desa Tarawali Kabupaten Ngada - Tali Wangge, Maria Carmelita; Dede Rua, Maria Oktavia; Api, Jefrianus; Ari, Sofia; Tamo Inya, Apliana (Abdimas Indonesian Journal, 2025)
Micro, Small and Medium Enterprises (MSMEs) are creative economic businesses owned by individuals or business entities. MSMEs in Tarawali Village have various forms such as banana and cassava chips businesses. The basic problem in this assistance is the lack of optimal packaging, labeling and marketing strategies that have an impact on the quantity and quality of production. The main objective of this service is to provide assistance in improving the quality of MSME products including marketing using the Participatory Action Research (PAR) method. The substance of this service is to provide assistance in packaging and labeling (brands) on banana chip business products that need to be branded so that they are more competitive in the market world and become an attraction for production such as brand creation or selection of packaging materials which are carried out by hearing with MSME actors. Assistance is also provided in digital marketing in terms of marketing strategies to increase the number of customers. The results of the service can be concluded that through this assistance, collective commitment in business can be increased, including the quality of packaging that affects product durability so as to provide satisfaction to consumers and potential marketing opportunities through digital marketing.